2017
DOI: 10.1111/1462-2920.13894
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Penicillium aurantiogriseum partiti‐like virus 1 to a new fungal host (Cryphonectria parasitica) confers higher resistance to salinity and reveals adaptive genomic changes

Abstract: We attempted to transfect six recently characterized virus species to protoplasts of Penicillium janczewskii and Chryphonectria parasitica. None of the recovered P. janczewskii colonies was positive for the transfected viruses, but Penicillium aurantiogriseum partiti-like virus 1 (PaPLV1) was detected in three distinct regenerated C. parasitica colonies. We screened the phenotype of the infected strains in up to 45 different conditions combining different media, salinity and temperatures: our results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 51 publications
2
47
0
Order By: Relevance
“…Also in such case, thanks to the presence of a mycovirus, the fungus displayed the overproduction of an effector which enhanced its virulence in the host plant. The hypothesis of positive interactions between fungi and viruses was further confirmed in other fungal‐virus interactions: in a first example, infection by a specific partitivirus brought to enhanced osmotic tolerance of C. parasitica; in a second example, infection with a distinct partitivirus enhanced mycotoxin production in Aspergillus ochraceus (Nerva et al ., , ). Another positive effect on the fungal host was reported during the interaction between a specific partitivirus and an isolate of Trichoderma harzianum : the virus infected isolate displayed an increased antagonistic activity if compared to the virus‐free isogenic isolate (Chun et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Also in such case, thanks to the presence of a mycovirus, the fungus displayed the overproduction of an effector which enhanced its virulence in the host plant. The hypothesis of positive interactions between fungi and viruses was further confirmed in other fungal‐virus interactions: in a first example, infection by a specific partitivirus brought to enhanced osmotic tolerance of C. parasitica; in a second example, infection with a distinct partitivirus enhanced mycotoxin production in Aspergillus ochraceus (Nerva et al ., , ). Another positive effect on the fungal host was reported during the interaction between a specific partitivirus and an isolate of Trichoderma harzianum : the virus infected isolate displayed an increased antagonistic activity if compared to the virus‐free isogenic isolate (Chun et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Five viruses identified in this analysis grouped with members of the genus Gammapartitivirus were identified that are phylogenetically related to an emerging group of partitiviruses that are separate from, but related to, the genus Gammapartitivirus (Fig 2); this group has been tentatively named Epsilonpartitivirus [41] . Identification of the PaPlV sequences was expected as this sample was RNA-seq data from Cryphonectria parasitica infected with PaPlV, previously isolated from P. aurantiogriseum by the same researchers [41] . To distinguish this viral genome from that isolated from the original host, the virus has been named PaPV1-cp.…”
Section: Gammapartitivirusmentioning
confidence: 94%
“…To distinguish this viral genome from that isolated from the original host, the virus has been named PaPV1-cp. Also, the slight modification of the virus name, from partiti-like to partitivirus, demonstrates a recent improved understanding that this is a partitivirus following the identification of a RNA segment encoding a putative CP [41] .…”
Section: Gammapartitivirusmentioning
confidence: 99%
“…RNAs (about 2 lg/lane) were separated in gel electrophoresis under denaturing conditions using glyoxal in HEPES-EDTA buffer as detailed in Sambrook and colleagues (1987). Hybridization were performed using a radiolabelled RNA probe prepared from EcoRI linearized purified plasmids containing cDNA fragments corresponding to both orientation (sense and antisense probes) of each of the 6 viruses through T7 transcription using the Maxiscript T7 kit reagents (Thermo Fisher Scientific Inc., Waltham, MA, USA), as detailed before (Nerva et al, 2017). In some cases, some fragments in specific orientations were toxic to E. coli after transformation, and recombinant plasmid could not be obtained.…”
Section: Northern Blotmentioning
confidence: 99%
“…External route of infection is apparently lacking; however, recent studies suggest that mycophagous insects function as mycovirus transmission vectors in the case of ssDNA mycoviruses (Liu et al, 2016). The infection by mycoviruses is often asymptomatic, but in some specific conditions alterations in the phenotype of the host fungus can be observed (van Diepeningen et al, 2006;Nerva et al, 2017). In some cases higher order biological interactions are also influenced; for example, the presence of a virus can lead to attenuation of virulence in a plant pathogenic fungus (Choi and Nuss, 1992) or can provide the capability to enhance thermal tolerance of the host plant to an endophytic fungus (M arquez et al, 2007).…”
Section: Introductionmentioning
confidence: 99%